COVID-19 and ECMO: the interplay between coagulation and inflammation—a narrative review - Mariusz Kowalewski; Dario Fina; Artur Słomka; Giuseppe Maria Raffa; Gennaro Martucci; Valeria Lo Coco; Maria Elena De Piero; Marco Ranucci; Piotr Suwalski; Roberto Lorusso (Critical Care, 2020)
Abstract Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has presently become a rapidly spreading and devastating global pandemic. Veno-venous extracorporeal membrane oxygenation (V-V ECMO) may serve as life-saving rescue therapy for refractory respiratory failure in the setting of acute respiratory compromise such as that induced by SARS-CoV-2. While still little is known on the true efficacy of ECMO in this setting, the natural resemblance of seasonal influenza’s characteristics with respect to acute onset, initial symptoms, and some complications prompt to ECMO implantation in most severe, pulmonary decompensated patients. The present review summarizes the evidence on ECMO management of severe ARDS in light of recent COVID-19 pandemic, at the same time focusing on differences and similarities between SARS-CoV-2 and ECMO in terms of hematological and inflammatory interplay when these two settings merge.